Chapter 1 Summoning the Heroes - wang, jiaren; Kanyu Wang, Regina (Taylor & Francis, 2022)
The chapter covers the difficulties that the director Frant Gwo, who rose to fame with My Old Classmate, faced when receiving the script for The Wandering Earth: distrust in the domestic market, the lack of experience related to science fiction films and the lack of local talent. With love, Frant Gwo assembled a team determined to make a truly localized and well-grounded Chinese science fiction film.